Analysis of the book of Chemistry for the middle third grade according to the skills of pivotal thinking - Saja Ahmed Awad al-Hawran, M.Dr. Afrah. Yassin Mohammed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The goal of this research is an analysis of the chemistry book for second-grade average, according to the thinking skills and axial and the goal of the search Formula Asia following :What are the key thinking skills included in the middle third-grade chemistry book?The researcher prepared a list of skills of pivotal thinking familiarized her with the literature and studies that dealt with the skills of pivotal thinking, as it was reached a list of skills as a preliminary form consisting of (8) main skills branching out from (21) qualitative skill, presented to a group of arbitrators and specialists in the teaching of chemistry, curricula and teaching methods and some. The researcher then analyzed the book of Chemistry for the third grade intermediate for the academic year (2020-2021) in the light of the list that was prepared and adopted the ideal unit for the analysis of both types (explicit and implicit) and repetition unit for multiplicity, and the stability of the analysis was calculated in agreement with external analysts and with the researcher herself, and the:1-order thinking skills axial chair in chemistry book for second grade expected in descending order (ticket - collecting information - analysis newborn – development-coding – integration – calendar)achieved this task by varying what several skills calendar unrealized.2-the repetitions of the central thinking skills in the book of Chemistry for the middle third grade (1,160).3-skill (remembering ) ranks first in the chemistry book for third-grade intermediate.In light of the findings of the study, the researcher came up with several recommendations and proposals, including1-balance in the proportions of including axial thinking skills in the chemistry book for the third-grade intermediate so that the skill does not cover the rest of the axial thinking skills.2-work to include the skills of the neglected boss in the chemistry book for the third grade intermediate.